PENGEMBANGAN E-LKPD BERBASIS SCIENCE, TECHNOLOGY, ENGINEERING AND MATHEMATICS (STEM) TERHADAP KETERAMPILAN PROSES SAINS SISWA PADA MATERI PERUBAHAN LINGKUNGAN KELAS X SMAN 1 TOHO - Siska (Program Studi Pendidikan Fisika, Fakultas Pendidikan MIPA & Teknologi, Universitas PGRI Pontianak, 2025)
This study aims to develop Science, Technology, Engineering And Mathematics-based E-LKPD on science process skills that are 1) valid 2) practical 3) effective. This research model uses the ADDIE development model by Tegeh et al (Analysis–Design-Development-Implementation-Evaluation). Data collection techniques: indirect communication, measurement and observation. The data collection tool uses expert validation sheets, questionnaires and tests. Research subject: grade 10 of SMA Negeri 1 Toho. Validity and practicality data analysis techniques using quantitative descriptive, effectiveness using data from pretest and posttest scores carried out by students The effectiveness criteria of E-LKPD are determined by the average value of the N-Gain score. The results of the study: 1) very valid with an average percentage of 85.72% 2) very practical with a student response percentage of 90.95% 3) effective average N-Gain of 0.71 Conclusion: E-LKPD based on Science, Technology, Engineering and Mathematics is classified as valid, practical and effective to be used in the learning process for students' science process skills.